Penerapan Peraturan Menteri Ketenagakerjaan Nomor 6 Tahun 2016 di PT. Braga Konsep Solusi - I Nyoman Gilang Radwithama; Anak Agung Sagung Laksmi Dewi (Jurnal Preferensi Hukum, 2021)
Braga Concept Solutions domiciled in Denpasar City is a company in the field of tourism, especially in restaurants. When approaching religious holidays, every worker/labourer gets non-wage income, namely the Hari Raya Allowance. However, the workers/laborers at PT. Braga Solusi Concept has not yet received the Religious Holiday Allowance as stipulated in the regulation. The purpose of this study is to reveal the application of the provision of religious holiday allowances for workers / laborers at PT. Braga Concept Solutions and obstacles in providing holiday allowances for workers/laborers at PT. Braga Solution Concept. The method used in this study is an empirical legal research method with a sociological juridical approach. The sources of law used are primary and secondary sources of law. In analyzing the data that has been collected then used qualitative analysis techniques. The results of the study reveal that the conclusion of this study is the mechanism for providing Religious THR at PT. Braga Concept Solutions are not fully in accordance with applicable regulations. The obstacle faced is the lack of information about the applicable regulations. Dissemination of laws and regulations is very necessary for workers with the aim of making workers aware of their rights, including the mechanism for resolving them if there are obstacles, the goal is to prevent this from happening again.